Integrating morphological and molecular taxonomy with the revised concept of Stelligeridae (Porifera: Demospongiae). Issue 1 (11th May 2019) - Morrow, Christine; Cárdenas, Paco; Boury-Esnault, Nicole; Picton, Bernard; McCormack, Grace; Van Soest, Rob; Collins, Allen; Redmond, Niamh; Maggs, Christine; Sigwart, Julia; Allcock, Louise A
Abstract: This study reinforces and extends the findings of previous molecular studies showing that there is a close relationship between species assigned to the sponge genera Halicnemia, Higginsia, Paratimea and Stelligera and that the family Heteroxyidae is polyphyletic. The present study has led to the description of one new species of Halicnemia and six new species of Paratimea, the resurrection of Halicnemia gallica and a better understanding of the characters uniting Stelligeridae. A new species of Heteroxya is also described. We demonstrate that many of the taxa assigned to Heteroxyidae are more closely related to other families, and we propose several changes to the classification of Heteroscleromorpha. Desmoxyidae is resurrected from synonymy and transferred to Poecilosclerida; Higginsia anfractuosa is transferred to Hymedesmiidae, and a new genus, Hooperia, is erected for its reception; Higginsia durissima is returned to Bubaris (Bubaridae); Higginsia fragilis is transferred to Spanioplon (Hymedesmiidae); Hemiasterella camelus is transferred to Paratimea ; and Raspailia ( Parasyringella ) australiensis and Ceratopsion axiferum are transferred to Adreus (Hemiasterellidae).